2018
DOI: 10.1093/pcp/pcy080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PSII Manganese-Stabilizing Protein Succinylation on Photosynthesis in the Model Cyanobacterium Synechococcus sp. PCC 7002

Abstract: Lysine succinylation is a newly identified protein post-translational modification and plays important roles in various biological pathways in both prokaryotes and eukaryotes, but its extent and function in photosynthetic organisms remain largely unknown. Here, we performed the first systematic studies of lysine succinylation in cyanobacteria, which are the only prokaryotes capable of oxygenic photosynthesis and the established model organisms for studying photosynthetic mechanisms. By using mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 98 publications
1
17
0
Order By: Relevance
“…Nowadays, several machine learning-based predictors have been employed to identify succinylation sites [54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70]. The SucPred [54] is the first succinylation site predictor, which was established by Zhao et al in 2015 through different encoding descriptors, including position amino acids weight composition, van der Waals volume normalized, grouped weight-based encoding, and auto-correlation functions, via SVM.…”
Section: Existing Prediction Modelsmentioning
confidence: 99%
“…Nowadays, several machine learning-based predictors have been employed to identify succinylation sites [54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70]. The SucPred [54] is the first succinylation site predictor, which was established by Zhao et al in 2015 through different encoding descriptors, including position amino acids weight composition, van der Waals volume normalized, grouped weight-based encoding, and auto-correlation functions, via SVM.…”
Section: Existing Prediction Modelsmentioning
confidence: 99%
“…In this study, the Wh parts of chimeric leaves had higher starch content and lower soluble sugar content, which suggested the Wh parts take a low photosynthetic rate and may act as a photosynthetic product sink. Previous studies have shown that lysine succinylation is prevalent in various photosynthetic organisms [8]. In this study, six succinylated proteins involved in photosynthesis were identified only in the Gr parts of chimeric leaves, including three subunits in photosystem I (PsaC, PsaD, PsaF), two subunits in photosystem II (PsbB, PsbP) and light-harvesting complex II chlorophyll a/b binding protein 2 (Lhcb2).…”
Section: Succinylated Proteins Involved In Cam Photosynthesis In the mentioning
confidence: 84%
“…PsbO is the largest extrinsic subunit of PSII, which plays critical roles in oxygen evolution reaction [36]. In cyanobacterium, PsbO succinylation can hinder correct interactions between PsbO and other PSII subunits by the conformation changes in the head domain of PsbO, leading to a negative regulation of oxygen evolution [8]. However, the Ksu sites in PsbO of Ananas comosus var.…”
Section: Succinylated Proteins Involved In Cam Photosynthesis In the mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these co-factors contribute to mechanisms for survival in iron-depleted environments (Palenik et al, 2003), such as the secretion of siderophores to chelate iron. In the form of the photosystem II manganese-stabilizing polypeptide (psbO), manganese plays a critical role in photosystem II function by catalyzing the light-induced dissociation of water to molecular oxygen (Bartsevich and Pakrasi, 1995;Liu et al, 2018). Inactivation of the manganese transport system (MNABC) leads to an invariable loss of activity in photosystem II, consequently affecting the photosynthetic process as a whole (Shcolnick and Keren, 2006 Table S4: Contributions of genes to variance, Related to Figure 3.…”
Section: Lasso Regressionmentioning
confidence: 99%